Human endogenous retroviruses and multiple sclerosis: Causation, association, or after-effect?. (July 2017) - Morandi, Elena; Tarlinton, Rachael E.; Tanasescu, Radu; Gran, Bruno
From the early days of MS discovery, infections have been proposed as a possible cause of the disease. In the last three decades, an association between human endogenous retrovirus expression and MS has been further investigated and confirmed. Nevertheless, the role of such retroviruses in the disease needs clarification. In this review, we introduce MSRV/HERV-W and describe its association with MS. We then summarize the evidence for the involvement of MSRV/HERV-W in the aetiology and progression of MS and its possible role as biomarker and drug target. Biological mechanisms for HERV effects in MS may involve the activation of innate immune pathways by the envelope protein of MSRV (MSRVEnv). In addition to in vitro and experimental studies, further insight on how HERVs may influence immune-mediated pathology in MS may also come from the use of antiretroviral treatments in patients.